2013
DOI: 10.1007/s11999-013-3032-5
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Low-dose Dexamethasone Reduces Postoperative Emesis and Pain After TKA: A Randomized Controlled Study

Abstract: Background Dexamethasone is a potent analgesic and antiemetic. However, the benefit of dexamethasone after TKA is unclear, as is the efficacy in a current multimodal regime. Questions/purposes We determined (1) whether the addition of dexamethasone to a protocol including ramosetron further reduces postoperative emesis compared with ramosetron alone; (2) whether it reduces postoperative pain; and (3) whether it increases the risk for wound complications in a current multimodal regime after TKA. Methods We rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
147
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(163 citation statements)
references
References 48 publications
16
147
0
Order By: Relevance
“…Five studies involving 435 patients reported VAS scores after 24 hours of rest. [16,1820,22] The pooled results indicated that IV steroids were associated with decreased VAS scores at 24 hours (MD = −10.21, 95%CI = −18.80 to −1.63, P  = .020, Fig. 4), and a high level of heterogeneity was identified ( I 2  = 95.9%, P  = .000).…”
Section: Resultsmentioning
confidence: 98%
“…Five studies involving 435 patients reported VAS scores after 24 hours of rest. [16,1820,22] The pooled results indicated that IV steroids were associated with decreased VAS scores at 24 hours (MD = −10.21, 95%CI = −18.80 to −1.63, P  = .020, Fig. 4), and a high level of heterogeneity was identified ( I 2  = 95.9%, P  = .000).…”
Section: Resultsmentioning
confidence: 98%
“…Two trials were excluded because they were not RCTs . Finally, 14 studies, with 542 patients in corticosteroid groups and 481 patients in control groups, were included in this meta‐analysis. The flow diagram is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Randomized sequence generation was implemented adequately in 8 studies; [6,9,18,2023,27] the other 5 studies had an unclear risk of bias. Allocation concealment was implemented adequately in all included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Allocation concealment was implemented adequately in all included studies. [6,9,18,2023,27] All studies reported blinding of the participants, personnel, and outcome assessors. [6,9,1727] The overall kappa value regarding the evaluation of risk of bias of included RCTs was 0.913, indicating an excellent degree of agreement between the 2 authors.…”
Section: Resultsmentioning
confidence: 99%